FAKTOR- FAKTOR YANG MEMPENGARUHI PERTUMBUHAN KENDARAAN BERMOTOR RODA DUA DI KOTA PEKANBARU - Muhammad Choirul Amin; Wahyu Hamidi; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the factors that influence the growth of two-wheel motor vehicles in the city of Pekanbaru. Data used in this study was a secondary character time series from 2005 to 2014, taking quarterly data. This research uses quantitative study using multiple linear regression analysis with significance level of 5% (0.05), which was applied to the computer program SPSS version 18.0. in this study performed statistical tests (t-test and test-f), the partial correlation coefficient and multiple determination coefficient test. The results showed that together simultaneously (Test F) population, income per capita, and the number of motor vehicle tax on the growth of two wheel motor vehicles amounted to 4.788 with a significance level of 0.049 and partially (t test) each also affect the growth of two-wheel motor vehicles with the results of the equation Y = -2,882,382.778 + 1.926 X1 + 0.259 X2 - X3 7.8054 affect a population of 2,763 with a significance of 0.047, per capita income effect on the growth of two-wheel motor vehicles amounted to 2,573 with significance 0.016 and the number of motor vehicle tax effect on the growth of two-wheel motor vehicles amounted to 0,260 -1.244 with significance. Predictive ability of the two variables are the number of two-wheeled motor vehicle growth was 70.5% (R2 = 0.705), as shown to us by the magnitude of adjusted R2, while the remaining 29.5% is influenced byother variables not included in this study.Keywords: population, income per capita, the number of motor vehicle tax and the amount of growth of two-wheel motor vehicles